Prenatal phenotype of Williams–Beuren syndrome and of the reciprocal duplication syndrome. Issue 2 (6th February 2014) - Marcato, Livia; Turolla, Licia; Pompilii, Eva; Dupont, Celine; Gruchy, Nicolas; De Toffol, Simona; Bracalente, Gabriella; Bacrot, Severine; Troilo, Enzo; Tabet, Anne C.; Rossi, Sabrina; Delezoïde, Anne L.; et al.
Key Clinical Message Copy losses/gains of the Williams–Beuren syndrome (WBS) region cause neurodevelopmental disorders with variable expressivity. The WBS prenatal diagnosis cannot be easily performed by ultrasound because only few phenotypic features can be assessed. Three WBS and the first reciprocal duplication prenatal cases are described with a review of the literature.